(3TQM bUjOI HGfJ SYGOs - (3cYH Hf RgjQ , CHh GdeZQH,J (B26 (3g` s
(3ChdgG (B:s
(3gjaGA ebHdg YLRGA eOHQg dG jTJci bUQ efgG hdG Whd s
(3BNQgG (B:s
(3JCNQJ CSJHbi GdMjGg ade CLO dfaSi MjGI eKd Cf CJbOeG hfSJZaQ Gddg JYGdi ef GdRjGOI hGdfbUGf JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3CHjGJ GdbUjOg eTchdg hGdeGOg ecJhHg Ydi YehOjf hHChQGbgG GdBNjQg JeRbs
(3fSNI QGHYIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B226s
Keywords: (3GdCOHs